2021
DOI: 10.1108/ejm-12-2019-0941
|View full text |Cite
|
Sign up to set email alerts
|

Using AI predicted personality to enhance advertising effectiveness

Abstract: Purpose The purpose of this study is twofold: first to demonstrate the application of an algorithm using contextual data to ascertain consumer personality traits; and second to explore the factors impacting the relationship between personality traits and advertisement persuasiveness. Design/methodology/approach A mixed-method approach that comprises two distinct yet complementary studies. The first uses quantitative methods and is based on a sample of 35,264 retail banking customers. Study 2 explores the fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 82 publications
0
12
0
Order By: Relevance
“…This more holistic assessment of the consumer using AI is less prevalent than preference construction. But recent research has demonstrated the potential of integrating personality traits to improve the personalization and persuasiveness of AI-based marketing (Shumanov et al 2021). More importantly, AI has shown great promise in deciphering consumers' personality traits from a variety of data.…”
Section: Personality Assessmentmentioning
confidence: 99%
“…This more holistic assessment of the consumer using AI is less prevalent than preference construction. But recent research has demonstrated the potential of integrating personality traits to improve the personalization and persuasiveness of AI-based marketing (Shumanov et al 2021). More importantly, AI has shown great promise in deciphering consumers' personality traits from a variety of data.…”
Section: Personality Assessmentmentioning
confidence: 99%
“…In this paper, bp model is used to analyze the cam of injection pump of single cylinder direct injection diesel engine. Through data simulation, through continuous bp network training, the best parameters are obtained, and the injection pump cam is optimally designed [15][16].…”
Section: Cam Of Single Cylinder Direct Injection Diesel Enginementioning
confidence: 99%
“…This coalescence presents many opportunities to integrate PC and ML, both to discover more about the effects of PC and to better tailor products and services to individuals. Technologies that currently use PC include AI agents, user profiling and predictive models, with applications in fields such as business, education, health and psychology (Shumanov et al , 2021; Wang et al , 2019; Yang et al , 2019; Zarouali et al , 2022).…”
Section: Introductionmentioning
confidence: 99%